Factors Associated With Stunting of Children at 24 Months in the AMANHI Pakistan Study. (14th June 2022) - Khan, Durray Shahwar; Jehan, Fyezah; Khalid, Farah; Shaheen, Fariha; Sheikh, Maheen
Abstract: Objectives: Malnutrition is a significant health problem among children in low- and middle-income countries. In 2017, 35% of children in South Asia were reported to be stunted. In Pakistan, 4 in every 10 children under 5 years are reported to be stunted. The aim of this study was to identify the factors associated with stunting amongst children 24 months of age, living in Pakistan, an LMIC. Methods: This is a secondary analysis of the AMANHI prospective cohort study. Newborns of mothers who were enrolled in the AMANHI-cohort were followed up to 24 months of life. Information on antenatal history, gestational age, sociodemographic and education, household hunger scale and food consumption status at 12 and 24 months was assessed. Anthropometry was done to evaluate length/height and weight using standardized methods. Logistic regression analysis was run using STATA (v.17.0) and odds ratios with 95% confidence interval were calculated. Results: In this prospective cohort study, 923 children were included with a gender distribution of 48.8% males and 51.2% females. The results of univariate analysis showed that the factors associated with stunting amongst children 24 months of age were: low birth weight (OR 2.23; 95% CI 1.61 to 3.10; P < 0.0001), small for gestational age (OR 2.07; 95% CI 1.54 to 2.78; p = 0), wealth falling in poorest quintile (OR 2.02; 95% CI 1.32 to 3.07; p = 0.001) or poor quintile (OR 1.62; 95% CI 1.07 to 2.45; p = 0.023), children who are Muslims (OR 1.87; 95% CI 1.15 to 3.07; p = 0.012), no maternal education (OR 3.22; 95% CI 1.53 to 6.77; p = 0.002), underweight mothers (OR 1.55; 95% CI 1.1 to 2.18; p = 0.013), and daily wage earning fathers (OR 1.4; 95% CI 1.03 to 1.9; p = 0.033). The consumption of dairy (OR 2.1; 95% CI 1.51 to 2.92; P < 0.0001) and sugar sweetened items (OR 1.79; 95% CI 1.32 to 2.44; P < 0.0001) were also found to be positively associated with stunting. However, there was no difference in odds of being stunted amongst children with poor/borderline or acceptable food consumption status at 12 and 24 months. Conclusions: The results of this study report the multitude of factors associated with stunting amongst children 24 months of age, residing in Pakistan. It also helps identify the different levels at which interventions can be targeted to reduce prevalence of stunting in this country. Funding Sources: None.